Optical Iridectomy as An Alternative Clear Visual Axis for Peters Anomaly - Laura Agnestasia; Julie Dewi i Barliana (Majalah Oftalmologi Indonesia, 2021)
Introduction and objective: Peters anomaly is a rare congenital disease presented with central leukoma, iridocorneal adhesion, and with or without a cataractous lens. The presence of central leukoma will block the visual axis and lead to a disruption in normal visual development. Therefore, optical iridectomy, which can overcome the high incidence of graft failure in penetrating keratoplasty (PK), has been proposed as the alternative treatment to clear the visual axis. This study aims to show the outcome of optical iridectomy in patients with Peters’ anomaly. Method: Systematic literature searched in Pubmed, Google Scholar, and Cochrane from their inception to August 2020 was conducted using keywords “iridectomy” and “Peters’ anomaly”. Full- text articles in English that report the outcome of iridectomy in Peters’ anomaly were included, and a manual review of article bibliographies was done. Outcome measures were analyzed using the following clinical questions: indication, age, visual acuity (VA), and intraocular pressure (IOP). Result: One case series and two case reports demonstrating the use of optical iridectomy in Peters anomaly were identified. In total, 26 patients aged one week to 7.7 years received optical iridectomy to establish a clear visual axis. All studies showed an improvement in visual acuity through clinical findings, and one of the studies showed a better postoperative VA in bilateral cases. Studies showed good control of IOP. Conclusion: Optical iridectomy can be used as a safe procedure to improve visual acuity in Peters anomaly patient.